Determinant factors of paying zakat on employment income by government servants in Malaysia / Shahiszan Haji Ismail, Jumaelya Jogeran and Prof. Madya Dr. Abd. Halim Mohd. Noor - Haji Ismail, Shahiszan; Jumaelya Jogeran; Mohd. Noor, Abd. Halim (Research Management Institute (RMI), 2012)
Zakat is an obligatory to all the Muslim. There are many instrument provide by zakat institution for Muslim people. However, are these obligations being practice by all the people? Especially to those government servants which have many facilities to pay the zakat. Based on statistic by the Pusat Pungutan Zakat, total amount of zakat payer around 78,820 on 2009, while on 2008 it is about 67,872 zakat payer. This amount only a small portion from 28.3 million of Malaysian population. A Muslim person at Malaysia is about 60% from the population. It shows that, many Muslim people at Malaysia still not perform their obligation to pay zakat as one of the Islamic pillar. There are many research and studies done by previous researcher regarding this never ending issue. It shows this topic is very important to be suit with the current situation. Even though there are many former study about the zakat, but there is lack of study at UiTM which majority of the staff are Muslim and for sure as a Muslim paying zakat is one of the obligatory that must be follow in Islam. Therefore, the objectives of this paper are, 1) To Identify level of zakat payment among the government staff at UiTM Melaka, 2) To analyse main factors which influence zakat payment among the government staff at UiTM Melaka. This research will use descriptive study to describe the characteristics of the variables of interest in a situation. Data will collect via survey questionnaires. Interview with expert person from zakat institution also as a method to gather the relevant information. Sample of the respondent will be choose randomly, it is only 200 academician staff from all the faculty, and about 100 non-academic staff from every department. Collected data will be analysing by using analysis descriptive and correlation. Multiple regression model and logistic regression are using to identify factors and possibility of respondent paying the zakat (Hairunizam 2005, Mohd Ali 2004, Kamil 2005). An outcome from the study expected to answer all the research questions and achieves the objective. It also hopefully can be published as a journal for the future.